The Effect of FMS Based Soccer Training on Elementary School Students’ Gross Motor Skills - Moch Ferdiansyah; Dinar Dinangsit; Muhammad Nur Alif (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2026)
This study aims to determine the effect of Fundamental Movement Skills (FMS) based soccer extracurricular training on the improvement of gross motor skills in 9–10 year old elementary school students in Bandung Regency. The study employed a quasi experimental design with a quantitative approach. The sample con-sisted of 30 students selected using purposive sampling. The instrument used was the Test of Gross Motor Development-3 (TGMD-3), which measures locomotor and manipulative skills. The FMS-based training program was delivered in a structured manner through movement activities such as running, jumping, balancing, drib-bling, and kicking a ball. The results of the study indicate that FMS based training has a positive effect on students’ gross motor skills. In the locomotor aspect, the horizontal jump and run skills were rated as excellent. In the manipulative aspect, the kicking skill showed the highest results compared to other skills. Overall, FMS-based soccer extracurricular training was able to improve elementary school stu-dents’ movement coordination, balance, agility, and object control. A structured training program tailored to children’s developmental stages was deemed effective for supporting Physical Education learning and early age sports develop-ment.